Bio‐Based Anti‐Biofoulant with Copper(II) as Intramolecular Catalyst for Radicals Formation - Jinbo Chen; Guangming Lu; Yu Hao; Yichao Lu; Liang‐Feng Huang; Yajie Zhang (Advanced Materials Interfaces, 2023)
Abstract Highly efficient and eco‐friendly antimicrobial agents are crucial to the development of future marine antifouling coatings. A high efficient and low bio‐toxicity bio‐based anti‐biofoulant, 2,5‐diformylfuran dioxime chelating with copper ions (E‐DFFD‐Cu), is evaluated. Its minimal bactericidal concentration and the concentration for 50% of maximal effect (EC50) are 4.95 and 7.03 µmol L−1, respectively. Excellent anti‐biofouling performance in marine environment in situ can be kept at least 90 days and with maximum release rate of copper ion of 0.01 µmol cm−2 d−1. Alkyl radical (R·) and hydrogen radical (H·) derived from E‐DFFD are enhanced via chelating copper(II) catalysis, which attracts and disrupts microbe cell membrane and pili between intimate cells, resulting in excellent anti‐biofouling effect. This provides a new perspective for developing anti‐biofoulant from anti‐biofouling mechanism in the future.